Calcifying Odontogenic Cyst with Complex Odontoma: Histological and Immunohistochemical Features - Mohsen Merati; Saeedeh Khajeh Ahmadi; Amin Rahpeyma; Nooshin Mohtasham (Mashhad University of Medical Sciences, 2012)
The calcifying odontogenic cyst (COC) is a rare odontogenic cyst. Only 2% of all odontogenic cysts and tumors are COC. COC associated with odontoma (COCaO) reported in 24% of COCs. COCaO presents a greater incidence in female, with a ratio of 2 to 1. The highest incidence of COCaO occurs during the second decade with a mean age of 16 years, most frequently occurring in the maxilla (61.5%). Here, we describe a classic case of COCaO of the maxillary incisor-canine region in 17-year-old girl, and discuss the clinicopathological features and immunohistochemical finding of this tumor.